2019
DOI: 10.1016/j.atherosclerosis.2019.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Apabetalone lowers serum alkaline phosphatase and improves cardiovascular risk in patients with cardiovascular disease

Abstract: Alkaline phosphatase (ALP) predicts residual cardiovascular risk in patients with cardiovascular disease on statin treatment.• Apabetalone treatment reduces circulating ALP in a dose-dependent fashion.• The reduction of circulating ALP by apabetalone is associated with a reduction in major adverse cardiovascular events (MACE).• The association of ALP reduction with MACE is independent of concurrent levels of high-sensitivity C-reactive protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 43 publications
2
30
1
Order By: Relevance
“…In this study, we demonstrate that apabetalone suppresses TNAP expression in liver cells (Supplemental Figs. 1A-B), the major source of circulating TNAP [26], which is consistent with reduced serum ALP observed in patients receiving apabetalone [13,14]. The present study also shows that apabetalone or JQ1 attenuates TNAP gene expression, protein levels and enzyme activity in VSMCs during osteogenic transdifferentiation (Figs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, we demonstrate that apabetalone suppresses TNAP expression in liver cells (Supplemental Figs. 1A-B), the major source of circulating TNAP [26], which is consistent with reduced serum ALP observed in patients receiving apabetalone [13,14]. The present study also shows that apabetalone or JQ1 attenuates TNAP gene expression, protein levels and enzyme activity in VSMCs during osteogenic transdifferentiation (Figs.…”
Section: Discussionsupporting
confidence: 89%
“…In CKD patients, apabetalone had favorable effects on kidney function evaluated by estimated glomerular filtration rate [13]. Apabetalone also reduced circulating alkaline phosphatase (ALP), a robust and independent predictor of all-cause mortality that contributes to VC progression [13,14]. Notably, a single dose provided to CKD patients rapidly resulted in reduction of several inflammatory cytokines, including IL-6 [15].…”
Section: Introductionmentioning
confidence: 99%
“…3,32,35,52,215,216 Moreover, clinical data collected to date show that safety is not a limiting factor for chronic dosing of apabetalone, supporting the use of BD2selective BETi in diseases outside of cancer. 32,214,215 Second, apabetalone trials have identified key pathways that benefit from BD2-selective BETi in cardiovascular and diabetes mellitus patients, 18,20,32,43,44,46 as well as chronic kidney disease patients. 47,217 This further underscores the role of BET proteins in driving the chronic maladaptive overexpression of genes and proteins which participate in networks and pathways that directly contribute to these disease states.…”
Section: Bd-selective Beti In the Clinic: What Human Data Do We Have?mentioning
confidence: 99%
“…Evidence is mounting to support the use of BETi in treating cancer, metabolic, inflammatory, neurologic, cardiovascular, and musculoskeletal diseases. [1][2][3]14,19,20,29,31,44,[50][51][52][53][54][55][56][57][58][59][60][61][62] Investigation of BETi potential as an antiviral has also recently garnered interest. [63][64][65][66][67] Unlike other reviews in the field, we focus this review on explaining why targeting BET proteins shows potential benefit in seemingly unrelated disease states.…”
Section: Introductionmentioning
confidence: 99%
“…RVX-208 counters the trans-differentiation and calcification of VSMCs [190]. RVX-208 lowers serum alkaline phosphatase levels and improves CVD risk [191]. RVX-208 favorably modulates the vulnerability of carotid artery plaque through ultrasonic measurement, which is related to an increase of HDL-P levels [192].…”
Section: Rvx-208 (Apabetalone)mentioning
confidence: 99%